Asymptotics of Solutions of the Generalized Hutchinson’s Equation - S. A. Kaschenko (Моделирование и анализ информационных систем, 2012)
We discuss the dynamics of the Hutchinson’s equation and its generalizations. An estimate of the global stability region of a positive steady state is obtained. The main results refer to existence, stability and asymptotics of a slow oscillating solution. New asymptotic methods are applied to a problem of dynamical properties of ODE system describing Belousov — Zhabotinsky reaction.